The abundance of Microcystis sp. on intensive shrimp ponds - Hayati Soeprapto; Heri Ariadi; Ubad Badrudin; Petrus H.T Soedibya (Depik, 2023)
Microcytis sp is plankton species that is detrimental in shrimp pond ecosystems. The purpose of this study was to detect the abundance of plankton and the presence of Microcystis sp. in the waters of vaname shrimp (L. vannamei) aquaculture ponds. The research method used is descriptive quantitative and qualitative with added analysis of dynamic modeling systems. The results showed that pond water quality conditions were still good enough for shrimp farming activities with details of dissolved oxygen 4.01-6.17 mg/L, pH 7.7-7.9, salinity 20‰, temperature 27.050-28.250C, nitrate 0.01-0.15 mg/L, phosphate 0.05-0.20 mg/L, brightness 25-35 cm. For the classification of plankton found among them are from the Bacillariophyceae class, there are the genera Skeletonema sp., Cyclotella sp., Coscinodiscus sp., and Amphipora sp., from the Chlorophyceae class, there are the genera Chlorella sp., Oocystis sp., and Clamydomonas sp., from the Cyanophyceae class. the genus Oscillatoria sp., Microcystis sp., and Anabaenopsis sp. The plankton diversity index (H') was obtained between 0.01-0.33 and the uniformity index (E) was obtained between 0.10-0.50, meaning that the condition of the pond waters is still quite good and there are minimal indications of pollution. The abundance of Microcystis sp. obtained between 0.2x104-0.6x104 cell/ml. from the results of dynamic modeling analysis it is shown that the abundance of Microcystis sp. in pond waters is influenced by the value of the productivity level of the waters and the process of grazing organisms. The results of this study can be concluded that the plankton abundance rate found in ponds ranges from 0.4x104-1.9x104 cell/ml which consists of 10 genera and 3 classes of plankton. Then Microcystis sp. its presence was found in 3 ponds with abundance rate ranging from 0.2x104-0.6x104 cell/ml.Keywords:CultivationGenusGrazingModelWaters